RANCANG BANGUN SISTEM INROMASI PENCARIAN DATA PENDAFTARAN SISWA SISWI PADA PAUD KB SABILUL IMAN PURWOKERTO BERBASIS WEBSITE - Yustina Yustina Yustina; Ria Manurung; Adi Wibowo (LPPM Poltek ST Paul, 2023)
PAUD KB Sabilul Iman, in providing services has not maximized the use of information technology, one of which is the new student registration system. As for the activities of the new student registration system found in PAUD KB Sabilul Iman, currently, the process of searching for student data is still being carried out by searching piles of bookkeeping that were previously used for recording new student data used for new student registration. From the results of the interviews that have been conducted, the problems that often occur are frequent errors (human errors) of student data being confused, data loss, and taking a long time in the process of managing student data so that employees cannot complete reports on time. Therefore, a Website-Based Information System for Searching Student Registration Data at Paud Kb Sabilul Iman was built. System development is carried out using the Prototype method, the PHP programming language, the Codeigniter framework, and database storage with MySQL. This research was also carried out until the testing process used the Wilcoxon signed test, black box testing, white box testing and benefit testing based on ISO 25010 standards. Based on the benefits test, the results obtained were Functional Suitability of 93.3%, Performance Efficiency of 98.35%, Reliability of 89.17%, Usability of 94.17%, and Maintainability of 94.9%. Thus it can be concluded that the Design of a Website-Based Search Information System for Searching Student Registration Data at Paud Kb Sabilul Iman Purwokerto can overcome problems in making reports and speed up the process of searching for student registration data at Paud kb Sabilul Iman Purwokerto.